2016
DOI: 10.1080/19382014.2016.1161874
|View full text |Cite
|
Sign up to set email alerts
|

Ginsenoside Rg3 prevents INS-1 cell death from intermittent high glucose stress

Abstract: Ginsenoside Rg3 protected INS-1 cell death from IHG with reducing apoptosis and increasing proliferation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…The intramuscular injection of 20(S)-Rg3 has more effects in vivo and in vitro (animal and phase I clinical research), higher bioavailability, and good continuous dosing security. Moreover, 20(S)-Rg3 is more suitable for application in clinical medicine, such as a novel inhibitor of autophagy [15] or protecting INS-1 cell death from intermittent high glucose [16]. It also has been confirmed that 20(S)-Rg3 is a compound that has many pharmacological effects such as anticancer [17], inhibition of brain injury [18], and diabetic kidney injury resistance [19].…”
Section: Introductionmentioning
confidence: 97%
“…The intramuscular injection of 20(S)-Rg3 has more effects in vivo and in vitro (animal and phase I clinical research), higher bioavailability, and good continuous dosing security. Moreover, 20(S)-Rg3 is more suitable for application in clinical medicine, such as a novel inhibitor of autophagy [15] or protecting INS-1 cell death from intermittent high glucose [16]. It also has been confirmed that 20(S)-Rg3 is a compound that has many pharmacological effects such as anticancer [17], inhibition of brain injury [18], and diabetic kidney injury resistance [19].…”
Section: Introductionmentioning
confidence: 97%
“…Ginsenoside Rb2 and its hydrolytic product ginsenoside Rg3 belong to the protopanaxadiol type of dammarane ginsenosides. Ginsenosides Rb2 and Rg3 have multiple functions in immune regulation, anti-oxidation, anti-inflammation, anti-aging and anti-fatigue ( Choi, 2002 ; Choi et al, 2015 ; Joo et al, 2015 ; Kim et al, 2016 ; Sun et al, 2017 ). However, their pro-angiogenic effects have not been vigorously studied, while their anti-angiogenesis along with anti-tumorigenic effects have been shown in several cancers ( Mochizuki et al, 1995 ; Joo et al, 2015 ; Sun et al, 2016 ; Sun et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, their pro-angiogenic effects have not been vigorously studied, while their anti-angiogenesis along with anti-tumorigenic effects have been shown in several cancers ( Mochizuki et al, 1995 ; Joo et al, 2015 ; Sun et al, 2016 ; Sun et al, 2017 ). As one of the few examples, related to pro-angiogenic effects, Kim et al reported that ginsenoside Rg3 at 1, 5, 10 µM was able to prevent INS-1 cell death by increasing cell proliferation ( Kim et al, 2016 ). Likewise, in our experimental conditions using HUVECs, ginsenoside Rg3 at lower concentrations (below 10 μM) markedly increased HUVEC proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…The cells were diluted with RPMI-1640 complete medium to approximately 2×10 5 /L, plated onto 6-well-plates, and then incubated at 37°C, 5% CO 2 , and 95% humidity for 48 h. After the culture reached 80% confluence, the medium was discarded, and cells were maintained in RPMI-1640 complete medium with different concentrations of glucose and FTZ serum. High-glucose induction of oxidative stress was conducted [ 28 ].…”
Section: Methodsmentioning
confidence: 99%